INTEGRASI DAN ISLAMISASI ILMU DALAM PERSPEKTIF PENDIDIKAN ISLAM - AMIN FAUZI (Universitas Muhammadiyah Prof Dr Hamka, 2017)
Integration and Islamization of knowledge is one of the main keys in manifesting the goal of Islamic education. The purpose of education is not just aimed at Muslims produce individuals who have intellectual achievement, but the most important is karimah. In the integration of Science and Islam, the scientific philosophical assumptions are not built on the philosophy of materialism, as modern science that raises a lot of havoc for humans. But it is built on unity and hierarchy exists, which gave it to the nation, to the recognition of the Oneness of God as the Creator of all creations in the universe.